On the spectral characterizations of 3-rose graphs - Wang, Jianfeng; Huang, Qiongxiang; Belardo, Francesco (Utilitas Mathematica, 2013)
A rose graph with p petals (or p-rose graph) is a graph obtained by taking p cycles with just a vertex in common. In this paper, we prove that all 3-rose graphs, having at least one triangle, are determined by their Laplacian spectra and all 3-rose graphs axe determined by their signless Laplacian spectra.